Analysis Of The Behavior, Preferences And Opinions Of The Younger Generation Towards E-Commerce And Demands For Closing E-Commerce - Leo Ivan; Farhan Farhan; Shandy Hadrianus Saragi; Ratuling Herman Yusuf (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The younger generation is the largest group of internet users, they are the first generation to grow up with computers, the internet, smartphones, online social media and online shopping. They tend to have similarities in their online shopping behavior. This research aims to analyze the behavior and preferences of the younger generation towards e-commerce and their opinions regarding demands for the closure of e-commerce by some people in Indonesia. This research is quantitative research using a questionnaire method with 22 respondents aged 17-25 years and from high school students to university students. The findings of this research show that the younger generation is more likely to use e-commerce for shopping and tends to reject demands to close e-commerce by some members of society. The implication of this research is that e-commerce must improve service quality, user experience, and transaction security to meet the needs and expectations of the younger generation.